2011
DOI: 10.5194/acp-11-8075-2011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a solar eclipse on photo-oxidants in different areas of China

Abstract: Abstract. This study investigates the effects of the total solar eclipse of 22 July 2009 on surface ozone and other photooxidants over China. A box model was used to study the sensitivity of ozone to the limb darkening effect during an eclipse event, and to show that the impact on ozone is small (less than 0.5 %). In addition, the regional model WRFChem was applied to study the effects of the eclipse on meteorological and chemical parameters, focusing on different regions in China. Chemical and meteorological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Finally, PAY and XIA show the largest delays with similar variations. In the first case, the minimum value is reached 1 h and 16 min after the MOT with an anomaly of −1.1 K. In the second case, the minimum temperature is shown with a shift of 11 min and a variation in −1.2 K. Wu et al (2011) reported similar temperature decreases during the same solar eclipse over China using the WRF-CHEM module. The amplitude of the temperature decrease in TAM is also in agreement with the WRF simulations in Greece shown by Founda et al (2007).…”
Section: A Montornès Et Al: Solar Eclipses In Wrf-arw Model 5957supporting
confidence: 52%
See 2 more Smart Citations
“…Finally, PAY and XIA show the largest delays with similar variations. In the first case, the minimum value is reached 1 h and 16 min after the MOT with an anomaly of −1.1 K. In the second case, the minimum temperature is shown with a shift of 11 min and a variation in −1.2 K. Wu et al (2011) reported similar temperature decreases during the same solar eclipse over China using the WRF-CHEM module. The amplitude of the temperature decrease in TAM is also in agreement with the WRF simulations in Greece shown by Founda et al (2007).…”
Section: A Montornès Et Al: Solar Eclipses In Wrf-arw Model 5957supporting
confidence: 52%
“…6) linked to high nonlinear relationships between the model dynamics and physical schemes. The particular variations in wind speed and direction during and after the eclipse are related to the degree of obscuration as well as the local environment and meteorological patterns, as it has been presented in other previous studies (Fernández et al, 1993b;Founda et al, 2007;Wu et al, 2011).…”
Section: A Montornès Et Al: Solar Eclipses In Wrf-arw Model 5957mentioning
confidence: 88%
See 1 more Smart Citation
“…Other previous work has found that the degree of O 3 loss during the eclipse is also a function of the O 3 /NO x ratio. Comparing data from polluted and clean sites, Wu et al (2011) found larger O 3 loss rates and higher NO 2 enhancements in polluted areas. Similar conclusions were derived in a comparison of eclipse data from four sites in Greece.…”
Section: Factors Driving the Trace Gas Behavior On The Eclipse Daymentioning
confidence: 88%
“…In previous works where the reduction of the incoming shortwave solar radiation, during solar eclipses, has been deemed as input for calculations, researchers apply the so‐called obscuration function, which takes into consideration the solar limb darkening effect (e.g., Eckermann et al, ; Hunt, ; Koepke et al, ; Outcalt & Meisel, ; Phillips, ; Svensson, ; Tzanis, ; Wu et al, ); others, however, have preferred using the occultation function, which focuses on only geometrical aspects (astrometric) of the solar disk's blocking, meaning that there is no limb darkening (e.g., Aplin & Harrison, ; Jagannathan et al, ; Korlarž et al, ; Vogel et al, ). The solar radiation differs from that of a hypothetical Sun without limb darkening up to around 50% at the 550‐nm wavelength according to Koepke et al ().…”
Section: The Occultation and Obscuration Functionsmentioning
confidence: 99%